PENGEMBANGAN ACADEMIC ENTREPRENEUR DI PERGURUAN TINGGI : PROSPEK DAN TANTANGAN - RAHARJA, SAMUN JAJA (AdBispreneur, 2018)
ABSTRACT The change in the management paradigm of higher education to become a financially independent institution, no longer relying on government subsidies and budgets, has has triggered efforts to make higher education more independent.  One concept that can be applied in that direction isAcademic Entrepreneur. This paper is intended to describe the various prospects and challenges in the development of Academic Entrepreneur. The method used in this study is qualitative method,Data collected through literature review and other secondary data. The results show that the development of Academic Entrepreneur has both prospects and challenges. It is suggested that universities begin mapping the readiness of academic entrepreneur development by using the scale of readiness calculation or unpreparedness in the development of academic entrepreneur Keywords: development, academic entrepreneur, prospect and challenge  ABSTRAKPerubahan paradigma pengelolaan Perguruan Tinggi untuk menjadi Lembaga yang mandiri secara finansial, tidak lagi mengandalkan subsidi dan anggaran pemerintah, telah memacu berbagai upaya untuk mewujudkan kemandirian perguruan tinggi. Salah satu konsep yang dapat diterapkan ke arah tersebut adalah Academic Entrepreneur. Tulisan ini ditujukan untuk mendeskripsikan tentang berbagai prospek dan tantangan dalam pengembangan Academic Entrpreneur. Metode yang digunakan dalam studi ini adalah metode kualitatif, Data dikumpulkan melalui kajian pustaka dan data sekunder lainnya. Hasil kajian menunjukkan bahwa pengembangan Academic Entrepreneur memiliki prospek dan sekaligus tantangan. Disarankan agar Perguruan Tinggi mulai melakukan pemetaan kesiapan pengembangan academic entrepreneur dengan menggunakan skala perhitungan kesiapan atau ketidaksiapan dalam pengembangan academic entrepreneur   Kata kunci : pengembangan, academic entrepreneur, prospek dan tantangan